Primates and protected areas in Suriname - Baal, Ferdinand L J; Mittermeier, Russell A.; van Roosmalen, Marc G.M. (Oryx, 1988)
Suriname is a small country, but it still has large tracts of undisturbed forests and rich wildlife. The authors discuss Suriname's plans to extend its already excellent network of protected areas and proposals to amend the hunting regulations. They also consider the country's eight monkey species, whose status can be regarded as indicative of that of the rest of the country's wildlife. © 1988, Fauna and Flora International. All rights reserved.